2001
DOI: 10.1182/blood.v97.4.886
|View full text |Cite
|
Sign up to set email alerts
|

A gene therapy approach for treating T-cell–mediated autoimmune diseases

Abstract: Experimental autoimmune encephalomyelitis (EAE) is a demyelinating disease of the central nervous system (CNS) that serves as a model for multiple sclerosis (MS) in humans. In mice, EAE is mediated by Th1 type CD4(+) T cells specific for various myelin proteins which migrate from the periphery to the CNS. Removal or blocking of CD4(+) cells before or shortly after disease induction was shown to prevent disease onset and/or disease progression but also results in general immune suppression. Most treatment regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 61 publications
1
38
0
Order By: Relevance
“…Factors that could alter the transport of the PIC to the nucleus did not overcome the p12-PM14 defect. Insertion of nuclear localization sequences (NLS), including the classical SV40 T antigen (TAg) NLS and the nonclassical KSHV LANA NLS (LANA [24][25][26][27][28][29][30][31][32] ), did not rescue MuLV p12-PM14, and neither showed tethering to the mitotic chromatin (Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
“…Factors that could alter the transport of the PIC to the nucleus did not overcome the p12-PM14 defect. Insertion of nuclear localization sequences (NLS), including the classical SV40 T antigen (TAg) NLS and the nonclassical KSHV LANA NLS (LANA [24][25][26][27][28][29][30][31][32] ), did not rescue MuLV p12-PM14, and neither showed tethering to the mitotic chromatin (Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
“…Gene therapy has not yet been attempted in MS, but there have been a number of studies in EAE that have invariably shown some level of efficacy at inhibiting the disease (Table 1), although in many cases this has only been an amelioration rather than elimination of disease. As the majority of the CNS is postmitotic, this puts constraints on the nature of the vector that can be used, and to date administration of plasmid DNA, [32][33][34][35][36][37][38][39][40][41] viral infection, [42][43][44][45][46][47][48][49][50][51][52][53] and retrovirally transduced cell (RVC)-carriers 47,[54][55][56][57][58][59][60][61][62][63] have been investigated in EAE (Table 1). These have largely focused on inhibition of the immune response either applied centrally to target the local pathological events within the CNS or peripherally administered to inhibit: initial sensitization, the activities of circulating cells or perivascular events in areas of local BBB breakdown.…”
Section: Gene Therapy In Autoimmune Demyelinating Diseasementioning
confidence: 99%
“…89 A number of approaches aimed at preventing the generation of encephalitogenic T cells have been assessed (Table 1). 32,[36][37][38]40,62,63 In some EAE models such as the PL/J mouse and Lewis rat, the disease is caused by activity of cells with very limited T-cell receptor (Tcr) subtype heterogeneity. Here, the majority of encephalitogenic cells express TcrVb8 90 and prophylactic, systemic DNA vaccination against this Tcr subtype has induced EAE amelioration.…”
Section: Systemic Vaccination Gene Therapy In Cns Autoimmunitymentioning
confidence: 99%
See 1 more Smart Citation
“…78 Collagen II-specific T-cell hybridomas modified to express an IL-12 antagonist were capable of ameliorating CIA. 79 Adoptive transfer of syngeneic B cells, transduced by fusion genes of autoantigens with IgG1 H chain, 80 or with lysosome-targeting Lamp-1 signal, 81 prevent and even cure animal models of diabetes and MS. Fibroblasts and arthritogenic splenocytes transduced to express soluble complement receptor 1 were therapeutic in mouse CIA. 82 Indeed, ex vivo retroviral strategies have already entered the clinic.…”
Section: Retroviral Vectorsmentioning
confidence: 99%